2010
DOI: 10.1111/j.1365-246x.2010.04660.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear to daily radon variability from continuous monitoring at the Amram tunnel, southern Israel

Abstract: S U M M A R YRadon is a naturally occurring radioactive noble gas generated within mineral grains of uranium bearing rocks by alpha decay from radium. The Amram tunnel (A. Bloch Geophysical Observatory) is a particularly suitable location for the investigation of radon variability. Located in the arid environment of the Arava desert, near Elat, the 170 m tunnel that constitutes the observatory enables radon monitoring in a desert environment and under fairly stable environmental conditions. The analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…Geophysical analysis of these relatively long time series measured with a high time resolution (within 1 h) demonstrates that Rn signals in air confined within rock units are characterized by systematic recurrence of signal patterns in the temporal, geological and geographical domains, at a depth of more than 100 m. The main types recognized are multi-year, annual radon (AR; periodic), MD and daily radon (DR; periodic) signals [14,15,25,34] as well as intense variation lasting several hours [16,17]. Examination of the patterns suggested that -variation patterns in the subsurface regime cannot be accounted for by simple and direct time varying processes in the gas system such as emanation, diffusion, absorption and advection; -absence of above surface atmospheric influence, in particular pressure; and -periodicity in the DR signal is characterized by solar tide frequencies S1 (24-h), S2 (12-h) and S3 (8-h) [31], implying an external above surface driving mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geophysical analysis of these relatively long time series measured with a high time resolution (within 1 h) demonstrates that Rn signals in air confined within rock units are characterized by systematic recurrence of signal patterns in the temporal, geological and geographical domains, at a depth of more than 100 m. The main types recognized are multi-year, annual radon (AR; periodic), MD and daily radon (DR; periodic) signals [14,15,25,34] as well as intense variation lasting several hours [16,17]. Examination of the patterns suggested that -variation patterns in the subsurface regime cannot be accounted for by simple and direct time varying processes in the gas system such as emanation, diffusion, absorption and advection; -absence of above surface atmospheric influence, in particular pressure; and -periodicity in the DR signal is characterized by solar tide frequencies S1 (24-h), S2 (12-h) and S3 (8-h) [31], implying an external above surface driving mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…At these levels, the air pressure regime is related to the local atmospheric barometric pressure while temperature tends to show stabile patterns reflecting the rock temperature at depth. Radon signals characterized by systematical recurrence of patterns in the temporal, geological and geographical domains have been reported from tunnels and boreholes in France [10], from Tenerife at a depth of more than 800 m [11][12][13] and from the desert in Israel at a depth of more than 100 m [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, borehole 2 exhibits a few large anomalies in radon concentration (e.g. in early and mid July) lasting for several days which are very similar to the radon signals described by Steinitz et al (2007) and Barbosa et al (2010). The results obtained are globally lower than usually observed for soils derived from the regional granite.…”
Section: Resultsmentioning
confidence: 41%
“…[70,75]). Radon time series can also display long-range dependence, as demonstrated in this issue by Donner et al [76].…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…[63,68,69]). Furthermore, investigation of radon variability in underground observatories such as the Bloch observatory in Israel [70], Gran Sasso in Italy [71], or the low-background laboratory in Belgrade [72], allows to go closer to natural conditions while keeping some control on environmental factors, particularly internal temperature. However, even under such idealized conditions, radon time series display complex temporal patterns usually characterized by strongly non-stationary daily, intra-seasonal and seasonal variability.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%